Changes of ceruloplasmin`s activity in animals` bronchi in late periods of experimental allergic alveolitis development and their correction with thiotriasolin - Mariana Ljubomurivna Baida (Journal of Education, Health and Sport, 2017)
The present study has shown that thiotriazolin possess to moderate antiinflammatory and antioxidant activities.An imbalance between generation of free radicals and antioxidant defences leads to a negative condition known as oxidative stress. Pulmonary damage caused by oxygen toxicity occurs due to the generation of reactive oxygen species and subsequent formation of more potent oxidants. Additionally, treatment with thiotriasolin has modulated enzymatic level of ceruloplasmin. The study of oxidative stress in the pathogenesis of exogenic allergic alveolitis could open new therapeutic horizons.